The role of cytoplasmic catalase in dehydration tolerance of Saccharomyces cerevisiae - França, Mauro Braga (Cell Stress Society International, 2005)
In this study, we investigated the role played by cytoplasmic catalase (Ctt1) in resistance against water loss using the yeast Saccharomyces cerevisiae as eukaryotic cell model. Comparing a mutant possessing a specific lesion in CTT1 with its parental strain, it was observed that both control and ctt1 strains exhibited increased levels of lipid peroxidation after dehydration, suggesting that catalase does not protect membranes during drying. Although the ctt1 strain has only 1 catalase isoform (peroxisomal catalase), the mutant showed the same levels of total catalase activity as the control strain. Furthermore, in cells deficient in Ctt1, the reduced glutathione:oxidized glutathione ratio (GSH: GSSG) of dry cells was higher than that of the control strain, indicating a compensatory mechanism of defense in response to dehydration. Even so, desiccation tolerance of the ctt1 strain was significantly lower than in the control strain. Using a fluorescent probe sensitive to oxidation, we observed that cells of the ctt1 strain showed levels of intracellular oxidation 70% higher than those of control strain, suggesting that Ctt1 plays a role in the maintenance of the intracellular redox balance during dehydration and, therefore, in tolerance against a water stress.